ANALISIS PENERAPAN AKUNTANSI LINGKUNGAN PADA UNIT PENGOBATAN PENYAKIT PARU-PARU KOTA PONTIANAK - B41111013, Kaana Ru'yah Malak kaana (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
ABSTRACT   This study aims to understand the theory and the concept of environmental accounting has been applied in a government agency. This study took place in Unit Treatment for Lung Disease Pontianak. This study used a qualitative descriptive method, data is taken based on interviews and observations at the Unit for Lung Disease Treatment Pontianak City for about 1 month. This research specifically focuses on the application of environmental cost accounting agencies to environmental problems caused by operating activities UP4 Pontianak, which consists of the identification, recognition, measurement, presentation and disclosure. Results of the study showed there was no special treatment in the reporting and presentation of environmental costs by the agency, and the agency has not made a specific policy related to the WWTP in the environmental management system. Unit Treatment for Lung Disease West Kalimantan serving embracing environmental costs Normative Model. Where the normative model recognizes and recording costs overall environment that is within the scope of the joint space generally account other allied accounts. The costs of these cognate inserted into subunits account certain costs in its financial statements.   Keywords: implementation of environmental accounting